Preparation of a Convertible Spacer Containing a Disulfide Group for Versatile Functionalization of Oligonucleotides. Issue 2 (25th February 2023) - Pontarelli, Alexander; Liu, Jiang Tian; Oh, Jung Kwon; Wilds, Christopher J.
Abstract: The protocols described in this article provide details regarding the synthesis and characterization of a disulfide containing linker phosphoramidite for terminal functionalization of synthetic oligonucleotides. The linker is first synthesized from 6‐mercaptohexanol in two steps and is incorporated at the 5′ end of short DNA oligonucleotides using automated solid‐phase synthesis. The linker contains a terminal tosylate group which is post‐synthetically displaced by altering the deprotection conditions to yield a variety of functional handles (N3, NH2, OMe, SH) or alternatively, the tosylate can be displaced directly with primary amines such as tert ‐butylamine. The linker system is also compatible with RNA oligonucleotides enabling the introduction of various functional handles (N3, NH2 ). The protocol outlined in this procedure provides access to a versatile linker for the terminal functionalization of oligonucleotides containing a disulfide bond which may serve useful in the synthesis of reduction‐responsive oligonucleotide conjugates. As a proof of concept, in this protocol the linker is used to modify a dT10 oligonucleotide and then conjugated by copper(I)‐mediated azide‐alkyne cycloaddition (CuAAC) to an alkyne‐modified poly(ethylene glycol) which shows concentration dependent release of the oligonucleotide upon treatment with 1, 4‐dithiothreitol, a reducing agent. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of disulfide linker phosphoramidite 3 Basic Protocol 2 : Synthesis, functionalization, and characterization of DNA oligonucleotides containing disulfide linker phosphoramidite 3 Basic Protocol 3 : Displacement of terminal tosylate functionalized DNA with primary aliphatic amines Basic Protocol 4 : Synthesis of oligonucleotide‐PEG conjugate Support Protocol : Preparation of PEG‐alkyne